2012
DOI: 10.1097/spv.0b013e3182686631
|View full text |Cite
|
Sign up to set email alerts
|

Urogynecological Causes of Pain and the Effect of Pain on Sexual Function in Women

Abstract: Female Sexual Dysfunction (FSD) is a complex biopsychosocial phenomenon. Screening, identifying and managing urogenital and sexual symptoms often result in significant improvement in women's quality of life. Providers must proactively question patients about possible presence of FSD. When a sexual problem is present, identify the type of FSD, counsel patients on the appropriate approaches to treatment. No single therapeutic approach is effective in treating all types of FSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 74 publications
0
17
0
4
Order By: Relevance
“…Overall, the research evaluated in this study provides an empirical foundation for considering sexual behavior, sexual functioning, and the treatment of sexual problems within a biopsychosocial framework . Within this review, a relatively substantial body of research emphasizes the biopsychosocial approach as an invaluable treatment framework for a wide range of sexual and sex‐related diagnoses, including male sexual dysfunction , female sexual dysfunction , and urological and gynecological conditions . Sex‐related pain disorders , especially among women , appear to be a specific area of focus in biopsychosocial treatment, with numerous research groups demonstrating evidence for the value of biopsychosocial and interdisciplinary, combinative treatment models .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the research evaluated in this study provides an empirical foundation for considering sexual behavior, sexual functioning, and the treatment of sexual problems within a biopsychosocial framework . Within this review, a relatively substantial body of research emphasizes the biopsychosocial approach as an invaluable treatment framework for a wide range of sexual and sex‐related diagnoses, including male sexual dysfunction , female sexual dysfunction , and urological and gynecological conditions . Sex‐related pain disorders , especially among women , appear to be a specific area of focus in biopsychosocial treatment, with numerous research groups demonstrating evidence for the value of biopsychosocial and interdisciplinary, combinative treatment models .…”
Section: Resultsmentioning
confidence: 99%
“…However, Dhingra et al reported some features about diagnosis and treatment of IC. It seems that diagnosis and treatment depended on being alert and skeptical as a physician . The treatments may only improve the patient's quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…diazepam suppositories. Trigger point injections provide temporary relief and have demonstrated varying levels of success [67,68]. More recently, botulinum toxin has been used to treat pelvic muscle floor spasm with demonstrated success [69][70][71].…”
Section: Myofascial Pelvic Pain Syndromementioning
confidence: 98%